Human skeletal muscle cell atlas: Unraveling cellular secrets utilizing 'muscle-on-a-chip', differential expansion microscopy, mass spectrometry, nanothermometry and machine learning. (February 2019) - Jena, Bhanu P.; Gatti, Domenico L.; Arslanturk, Suzan; Pernal, Sebastian; Taatjes, Douglas J.
Highlights: Establishing a human skeletal muscle cell reference atlas utilizing 'Muscle-on-a-Chip'. 'Differential Expansion Microscopy'. 'Mass Spectrometry'. 'Nanothermometry' and 'Machine Learning'. to facilitate precise deconvolution of subcellular organelle features in disease detection. Abstract: The 'Human Cell Atlas' project has been launched to obtain a comprehensive understanding of all cell types, the fundamental living units that constitute the human body. This is a global partnership and effort involving experts from many disciplines, from computer science, engineering to medicine, and is supported by several private and public organizations, among them, the Chan Zuckerberg Foundation, the National Institutes of Health, and Google, that will greatly benefit humanity. Nearly 37 trillion cells of various shapes, sizes, and composition, are precisely organized to constitute the human body. Humans, like all other living organisms, are dynamic, and therefore a comprehensive understanding of different cells in their various dynamic states is required to provide a reference map for the early diagnosis and various preventive approach to disease, and in the development of precision therapeutics. Skeletal muscles being the most abundant tissue and the largest locomotor and metabolic organ in the human body, requires a global understanding of its structure, composition, and function. The objective of creating a 'Human Skeletal Muscle Cell Atlas', necessitates therefore a comprehensive understanding of the emergent properties of skeletal muscle cell growth, development, structure, function and chemistry, under conditions of activity and inactivity. To achieve this objective would require a very precise yet rapid and cost-effective approach of combined multimodal imaging, including our new and novel 'Differential Expansion Microscopy', our 'Nanoscale Thermometry', combined with 'Mass Spectrometry', 'Motor Protein Motility Assay' and 'Machine Learning' tools.